Exploring support for LGBTQ youth transitioning from foster care to emerging adulthood. (December 2020) - Paul, June C.
Highlights: Limited research exists on LGBTQ youth leaving foster care as adults. LGBTQ transition-age youth described the sources and types of support they received. Many LGBTQ youth indicated child welfare professionals in their support networks. Key deficits included a lack of attention to safety and access to essential services. Potential implications for child welfare policy, practice, and research are provided. Abstract: Former foster youth are often uniquely disenfranchised, as many suffer from a lack of support (e.g., financial, informational, emotional) resulting from their involvement in foster care. Although all youth who exit foster care as adults may have difficulty accessing the support they need to become healthy-functioning adults, these issues may be exacerbated for LGBTQ (lesbian, gay, bisexual, transgender, queer and questioning) youth who face added health and wellbeing challenges associated with their sexual and/or gender minority statuses. This study used face-to-face, qualitative interviewing and eco-mapping techniques to explore the experiences and perspectives of 21 LGBTQ foster youth, ages 17–21, to identify and describe who provides them with support, the kinds of support they have received, and whether there were any specific support-related needs and challenges they may be experiencing during this critical time. Results revealed that although many LGBTQ foster youth included a variety of child welfare professionals (e.g., caseworkers, foster parents) and other service providers (e.g., teachers, therapists) within their support networks, the majority experienced several unmet needs and challenges—most of which were associated with their sexual and/or gender minority statuses. Multiple themes were identified, including a lack of attention to safety and protection from risks of harm and access to essential care and services (e.g., LGBTQ affirming health care, safe and supportive housing, LGBTQ community-based resources, guidance related to LGBTQ identity development). Results provide initial understanding and awareness of some of the support-related issues and challenges faced by these youth, and help to build a framework of knowledge from which to develop further hypotheses regarding how LGBTQ youth are faring in our nation's child welfare system. Implications for child welfare policy, practice, and research are discussed.